Bridge management 4 inspection, maintenance, assessment and repair - Ryall, M. J.; Parke, G. A. R.; Harding, J. E. (Thomas Telford, 2000)
These proceedings represent the tremendous amount of research that has gone into improving ways of tackling the tasks associated with sound bridge management. It consists of 93 papers, covering advanced bridge management systems; monitoring risk and reliability analysis, and rehabilitation.
Conference proceedings.
Keywords: Bridges -- Maintenance and repair -- Management -- Congresses.; Bridges -- Inspection -- Congresses.; elektronické knihy; electronic books